2012
DOI: 10.1371/journal.pone.0037206
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of the Incidence of HFMD and Seroepidemiology of Antibodies against EV71 and CoxA16 in Prenatal Women and Their Infants

Abstract: BackgroundHand, foot, and mouth disease (HFMD) has been emerging as an important public problem over the past few decades, especially in Asian and Pacific regions. A national program on EV71 vaccine development against HFMD was initiated in China, in 2008, which called for a need for seroepidemiological study for the target population.Methodology/Principal FindingsThis was a retrospective study conducted in Jiangsu Province, in October, 2010. We measured the neutralizing antibodies against EV71 and CoxA16 in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 24 publications
(28 reference statements)
7
61
2
Order By: Relevance
“…Maternal antibodies against CA16 and EV71 were found to decline to the lowest level (CA16: 26.4%, 1:7.3; EV71: 41.3%, 1:11.3) in 7-mo-old infants from Jiangsu Province, and then gradually increase to high levels (CA16: 54.3% and 1:24.3; EV71: 56.2% and 1:35.3) at 27-30 mo of age. 49 In Ningbo, the positive rate of neutralizing antibodies against CA16 and EV71 was 43.2% and 13.5%, respectively, in 1-y-old infants, and increased to 67.6% and 67.6%, respectively, in the 5-y-old group. 48 The positive rate in the 5-y-old group was similar to the adult level.…”
Section: Seroepidemiology Of Ca16mentioning
confidence: 91%
See 3 more Smart Citations
“…Maternal antibodies against CA16 and EV71 were found to decline to the lowest level (CA16: 26.4%, 1:7.3; EV71: 41.3%, 1:11.3) in 7-mo-old infants from Jiangsu Province, and then gradually increase to high levels (CA16: 54.3% and 1:24.3; EV71: 56.2% and 1:35.3) at 27-30 mo of age. 49 In Ningbo, the positive rate of neutralizing antibodies against CA16 and EV71 was 43.2% and 13.5%, respectively, in 1-y-old infants, and increased to 67.6% and 67.6%, respectively, in the 5-y-old group. 48 The positive rate in the 5-y-old group was similar to the adult level.…”
Section: Seroepidemiology Of Ca16mentioning
confidence: 91%
“…30 A follow up study of 975 infants under 3 y old found that 143 infants presented with HFMD during the follow-up period. 49 The titers of neutralizing antibodies against CA16 and EV71 increased by 4-fold in 90 cases (62.9%) and 99 cases (69.2%), respectively. Fifty-four cases (37.8%) showed an increase in neutralizing antibodies against both CA16 and EV71.…”
Section: Molecular Epidemiology Of Ca16mentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, EV71-associated disease are usually mild and self-limiting, so mild cases could be underreported significantly if patients did not seek for medical care. 23 If a case capture strategy detects moderate to severe cases easier than mild cases, or detects cases with typical symptoms easier than those with nonspecific symptoms, and if vaccinated cases are milder or more atypical than placebo cases, this will result in a too high efficacy estimate. 15 Therefore, in order to avoid missed EV71-associated cases, the active surveillance system we built in the efficacy trial covered all possible cases with suspected clinical symptoms without an obvious cause, by excluding only those with a definite other cause such as burning, traffic accident and so on.…”
Section: Detection Of Potential Ev71-associated Cases Via Clinical Mamentioning
confidence: 99%